Konglish : Cross-linguistic lexical issues for Korean learners of English - Nam, Hyun-Jeong (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2009)
The present study investigated ow the mental lexicon of Korean learners of English is organized, and, in particular, how resources required to comprehend and produce English are stored and accessed in their mental lexicon and whether the L1 mediates the process. Konglish, the unique interlanguage of Korean learners of English, arising from their impoverished knowledge of English and influence from Korean, was drawn into the picture as a means of reflecting whether/how L1 knowledge in involved in the process of the organization of their mental lexicon.
Keywords: Applied Linguistics, Ph.D.; Ph.D. Trinity College Dublin